Cohort Studies on Chronic Non-communicable Diseases Treated With Traditional Chinese Medicine: A Bibliometric Analysis - Li, Yiwen; Liu, Yanfei; Cui, Jing; Zhao, Hui; Liu, Yue; Huang, Luqi (Frontiers in Pharmacology, 2021)
To quantitatively and systematically analyze the current status and future trend in the development of the application of cohort studies in the prevention and treatment of chronic non-communicable diseases (NCDs) by traditional Chinese medicine (TCM). Strict inclusion and exclusion criteria were used to search publications from PubMed, Embase, Cochrane Library, and CNKI(China National Knowledge Infrastructure) databases for cohort studies on NCDs with TCM as the main intervention since the establishment of these databases. Information on the year of publication, exposure factors, diseases, and outcome indicators was obtained, and literature quality assessment and bibliometric descriptive analysis were carried out. A total of 177 published articles were included, involving 1,610,873 cases. There were 108 non-prospective cohort studies and 69 prospective cohort studies. The diseases involved in the cohort studies were, in order of the number of published articles: malignant tumors (81 articles, 45.76%, for which a systematic summary was performed), cardiovascular diseases (34 articles, 19.21%), neurological diseases (28 articles, 15.82%), chronic kidney diseases (16 articles, 9.04%), cirrhosis (8 articles, 4.52%), diabetes mellitus (7 articles, 3.95%), and chronic respiratory diseases (4 articles, 2.26%). The study participants were mainly from mainland China (119 articles, 67.23%), Taiwan (56 articles, 31.64%), and Hong Kong (1 article, 0.56%). The number of cohort studies increased significantly in the last 5 years (65 articles, 36.72%), and after the Newcastle-Ottawa Scale (NOS) literature quality evaluation, the number of articles that received a score of 4-5 was high (112 articles, 57.63%), and the overall quality needs to be improved. The application of cohort studies in the field of TCM for the prevention and treatment of NCDs has developed rapidly in the past five years, focusing on the prevention and treatment of tumors as well as cardiovascular and cerebrovascular diseases. However, the design and implementation of cohort studies still have great limitations, and in the future, we should actively cooperate with evidence-based methodologists and standardize the implementation, which will help provide more clinical evidence and give full play to the characteristics of TCM.